Revisión sistemática sobre la bacteria Stafhylocuccus pseudointermedius relacionada a problemas zoonóticos - Mora Martínez, Jonathan Patricio (2018)
The genus Staphylococcus, is part of a large group of species that act as opportunistic pathogens, responsible for causing different diseases of importance in veterinary and human medicine. Among the most representative and important Staphylococcus is Staphylococcus pseudintermedius coagulase positive, which is a bacterial commensal skin and mucous of dogs and cats, is considered an opportunistic pathogen responsible for a wide range of infections such as: pyoderma, otitis, infections in the urinary tract, bone and postoperative wounds in pets. In the present investigation, a systematic review was carried out on the S. pseudintermedius bacterium, using scientific articles published from January 1, 2012 to January 31, 2018 in documentary sources such as PubMed and ScienceDirect, obtaining a total of 40 articles for this review. Obtained as a result, the bacterium Staphylococcus pseudintermedius has a high zoonotic potential and causes various pathologies in humans, which have had frequent contact with pets after surgical wounds or bites, being the owners of pets and veterinarians the main affected, Staphylococcus pseudintermedius has been treated and erroneously identified by human doctors, because it is confused with Staphylococcus aureus, since they present characteristics and produce similar pathologies, on the other hand it was determined that this bacterium is not considered as an emerging zoonotic agent, since there was no relevant information on the subject or the risk factors that may have.